Exploring oxypropylation to prepare liquid and biphasic polyols from the pine-fruit shell of Auraucaria angustifolia - Pinto, J.A. (2017)
This work comprises the characterization of pine-fruit shell, the residue of the edible seeds of Araucaria angustifolia, a coniferous tree native of South America with economic importance in the South and Southwest of Brazil, and their subsequent use to produce polyols trough oxypropylation. Two different alternatives have been followed: (i) total oxypropylation to produce liquid polyols and (ii) partial oxypropylation to produce biphasic polyols (liquid polyols reinforced with biomass of the same nature). The first polyols were characterized in what concerns unreacted biomass, homopolymer content, hydroxyl number and viscosity, and their properties compared with equivalent products to foresee future applications (e.g. production of rigid polyurethane foams). The second ones were subjected to homopolymer extraction and tested to produce composite materials by hot pressing.